Knowledge, attitude, and practice among the Indian population regarding COVID-19 using LASI-DAD COVID-19 data - Saritha, Ala; Jangra, Rohit; Bhat, Lekha; Philip, Neena Elezebeth (International Journal of Public Health Science (IJPHS), 2025)
During the COVID-19 pandemic, India was one of the worst-hit countries in terms of the number of cases and deaths. Knowledge, attitude, and practice play an important role in reducing disease transmission. This study uses a nationally represented large data set to understand the knowledge, attitude, and practice (KAP) of COVID-19 among the Indian population. This cross-sectional study utilized Diagnostic Assessment of Dementia for the Longitudinal Aging Study in India (LASI-DAD) COVID-19 data which provides information on respondents’ demographics, socioeconomic effects, health status, behavior, perceptions, and attitudes toward COVID-19. Descriptive statistics, correlation, and regression were performed to find the results. Out of 3,797 respondents, 1,929 (50.8%) accounted for males and 1,868 (49.2%) for females; rural respondents were 40.3% and urban were 59.7%. The findings show that the respondent’s knowledge about COVID-19 was improved from rounds 1 to 4 and 7, but attitude from round 2 to round 8 and behavior from round 1 to round 9 were poor. In multivariate analysis, males (AOR=1.855; CI=1.129-3.048; p=0.015) and people residing in urban areas (AOR=1.698; CI=1.050-2.745; p=0.031) had a good level of knowledge towards COVID-19 when compared to their females, and rural counterparts. Despite a good level of knowledge about COVID-19 among the Indian population, attitudes and practices towards COVID-19 were poor. There is a need to establish and implement effective policies and interventions to improve people’s behavior towards COVID-19 and similar pandemics that the world might encounter in the future.